PENGARUH KUALITAS KEHIDUPAN KERJA DANKEPEMIMPINAN YANG MELAYANI (SERVANT LEADERSHIP) TERHADAP KINERJA DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) SEBAGAI MEDIASI (Studi di Kantor Kecamatan Juwana Kabupaten Pati) - Sujarta, 1342020016 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to identify and analyze the influence of Quality of Work Life and servant leadership on Performance which Mediatied by Organizational Citizenship Behavior (OCB) in District Office Juwana of Pati regency. The research data was obtained from the questionnaire (primary) on the Quality of Work Life as X1, servant leadership asX2, OCB as Y1 and Performance as Y2 and through census in this research amount to 83 people. The technique of testing data used in this study include the validity and reliability, multiple regression analysis and t test to prove the hypothesis of the research, as well as mediation test. The results showed; there is positive and significant impact the quality of working life on OCB (0,000), there is a positive and significant influence of servant leadership on OCB (0,000), there is a positive and significant influence quality of work life on the performance of employees (0,004), there is a positive and significant influence servant leadership on employees performance (0,021), OCB has positive and significant impact on employees performance (0,000), OCB mediated effect of the quality of work life on employee performance (indirect effect> direct effect (0.248> 0.232)), OCB mediated effect of servant leadership to employee performance (indirect effect> direct effect (268> 0.189)). District Head Juwana of Pati regency provide exemplary leadership should serve well, creating a satisfying work life quality, and increase OCB good for improving the quality and performance of employees Keywords: Quality of Work Life, servant leadership, organizational citizenship behavior (OCB), Performance